Quality of Life Difference between Children with Obesity and Children without Obesity - Nelsi Marintan Tampubolon; Endang Dewi Lestari; Andri Iryawan; Siti Munawaroh (Smart Society Empowerment Journal, 2022)
ABSTRACTIntroduction: Obesity has become a global health problem because obesity is widespread in many countries and needs to be addressed immediately. Obesity can happen to anyone, including children and adolescents. Obesity in children can affect physical and mental conditions that can affect the quality of life. This study aims to determine whether there are differences in the quality of life of obese and non-obese children in Warga Junior High School SurakartaResearch Methods: An analytical observational study with a cross-sectional approach involved 66 students who were divided into 2 groups. Each group consisted of 33 students who were determined by the purposive sampling technique. Weight measurement was carried out to obtain data on obesity status, while the quality of life of students was measured by the Pediatric Quality of Life Inventory (PedsQL) score version 4.0. The data obtained were analyzed by unpaired t-test.Results: The obese and non-obese children had a mean PedsQL score of 78,385 and 83,807, respectively. The unpaired t-test in both groups showed a p-value of 0.056.Conclusion: The quality of life of obese and non-obese students Warga Junior High School Surakarta was not significantly different.Keywords: Quality of life; obesity; children; adolescentP